2011
DOI: 10.1162/jocn_a_00026
|View full text |Cite
|
Sign up to set email alerts
|

Face Processing Changes in Normal Aging Revealed by fMRI Adaptation

Abstract: We investigated the neural correlates of facial processing changes in healthy aging using fMRI and an adaptation paradigm. In the scanner, participants were successively presented with faces that varied in identity, viewpoint, both, or neither and performed a head size detection task independent of identity or viewpoint. In right fusiform face area (FFA), older adults failed to show adaptation to the same face repeatedly presented in the same view, which elicited the most adaptation in young adults. We also pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 89 publications
2
58
0
Order By: Relevance
“…This result is consistent with the idea of a compensatory mechanism whereby additional activity in task-relevant regions increases the ability of older adults to carry out the task. Similarly, another experiment examined face perception 48 and found a set of regions in right PFC and occipital cortex where increased activity was associated with better face recognition in older adults, but not a younger group. Furthermore, in a task requiring attention to right and left visual fields 49 , only old adults showed increased activity in bilateral PFC that was positively correlated with better performance.…”
Section: Compensation In the Older Brainmentioning
confidence: 98%
See 1 more Smart Citation
“…This result is consistent with the idea of a compensatory mechanism whereby additional activity in task-relevant regions increases the ability of older adults to carry out the task. Similarly, another experiment examined face perception 48 and found a set of regions in right PFC and occipital cortex where increased activity was associated with better face recognition in older adults, but not a younger group. Furthermore, in a task requiring attention to right and left visual fields 49 , only old adults showed increased activity in bilateral PFC that was positively correlated with better performance.…”
Section: Compensation In the Older Brainmentioning
confidence: 98%
“…Moreover, discrimination thresholds for distinguishing same from different faces were correlated with the degree of adaptation in the FFA across younger and older adults, indicating that this adaptation was important for behavior. A similar study 48 assessed adaptation in the FFA during presentation of faces that also varied in viewpoint (right/left orientation). Young adults showed the least activity when the same face was seen in the same viewpoint, more activity when the face or the viewpoint changed, and the most activity when both the face and viewpoint changed.…”
Section: Dedifferentiationmentioning
confidence: 99%
“…Previous studies that showed age-related difficulties in facial emotion identification have examined associations of this deficit with age differences in functional brain activation (Fischer et al, 2005, 2010; Gao et al, 2009; Lee et al, 2011; Ebner et al, 2012). It is proposed that multiple brain regions work together in order for face processing, independent of emotional valence, to occur (for review see Ruffman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of such additional areas may help compensate for age-related decline in the face processing network. Interestingly, Lee et al (2011) noted that "high performing" older adults (i.e., based on faster RT performance in a face matching task conducted outside the scanner) recruited a similar face network as younger adults. However, activation in this network was not suf ficient to support the matching of identity across views, as older adults who engaged this network did not reliably exhibit faster response times in this condition.…”
mentioning
confidence: 99%